Long Noncoding RNA HOTTIP Promotes Nasopharyngeal Cancer Cell Proliferation, Migration, and Invasion by Inhibiting miR-4301 - Shen, Meiqin (Med Sci Monit, 2019)
BACKGROUND: The long noncoding RNA (lncRNA) HOTTIP is involved in gastric cancer tumorigenesis, papillary thyroid carcinoma, colorectal cancer, lung adenocarcinoma, and hepatocellular carcinoma, but it is unclear how HOTTIP exerts roles in nasopharyngeal carcinoma (NPC). The present study investigated HOTTIP function during NPC development. MATERIAL/METHODS: HOTTIP levels in cancer specimens and cell lines were analyzed using qRT-PCR. HOTTIP function in NPC was determined by Cell Counting Kit-8 (CCK8) and Transwell assay. RESULTS: HOTTIP expression was increased in NPC tissues. Higher levels of HOTTIP are correlated with lower survival in NPC patients. HOTTIP silencing suppressed the proliferation, cell cycle, migration, and invasion of NPC cells. HOTTIP served as a sponge for miR-4301. miR-4301 expression was significantly inhibited by HOTTIP in NPC cells. miR-4301 overexpression dramatically inhibited NPC cell proliferation, migration, and invasion. CONCLUSIONS: This study showed that HOTTIP acts as an oncogene in NPC by sponging miR-4301.